Optimization of Image Quality and Organ Absorbed Dose for Pediatric Chest X-Ray Examination: In-House Developed Chest Phantom Study - Thanyawee Pengpan; Natch Rattanarungruangchai; Juthathip Dechjaithat; Phawinee Panthim; Puntarika Siricharuwong; Ausanai Prapan (Radiology Research and Practice)
Purpose. This study aimed to identify proper exposure techniques to maintain optimal diagnostic image quality with minimum radiation dose for anteroposterior chest X-ray projection in pediatric patients. Methods. Briefly, an in-house developed pediatric chest phantom was constructed. Next, nanodot OSLDs were used for organ absorbed dose measurement and placed in the lung area, and the phantom was exposed to various exposure techniques (ranging from 50 to 70 kVp with 1.6, 2, and 2.5 mAs). After that, the phantom was used to assess image quality parameters, including SNR and CNR. Two radiologists assessed the subjective image quality using a visual grading analysis (VGA) technique. Finally, the figure of merit (FOM) was analyzed. Results. The developed phantom was constructed successfully and could be useful for dose measurement and image quality assessment. The absorbed dose varied from 0.009 to 0.031 mGy for the range of exposure techniques used. SNR and CNR showed a gradually increasing trend, while kVp and mAs values were increased. The highest kVp (70 kVp) produced the highest SNR and CNR, exhibiting a significant difference compared with 50 and 60 kVp (P<0.05). The overall VGA score was 3.2 ± 0.3, and the low kVp technique demonstrated better image quality compared with the reference image. Conclusion. The optimized exposure technique was identified as 60 kV and 2.5 mAs, indicating the highest FOM score. This work revealed practicable techniques that could be implemented into clinical practice for performing pediatric chest radiography.